2020
DOI: 10.1155/2020/4251761
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Hub Genes Related to Diagnosis and Prognosis of Hepatitis B Virus‐Related Hepatocellular Carcinoma via Integrated Bioinformatics Analysis

Abstract: Hepatocellular carcinoma (HCC) is a common malignant cancer with poor survival outcomes, and hepatitis B virus (HBV) infection is most likely to contribute to HCC. But the molecular mechanism remains obscure. Our study intended to identify the candidate potential hub genes associated with the carcinogenesis of HBV-related HCC (HBV-HCC), which may be helpful in developing novel tumor biomarkers for potential targeted therapies. Four transcriptome datasets (GSE84402, GSE25097, GSE94660, and GSE121248) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…In a previous study, we reported 17 hub genes with diagnostic and prognostic values in HBV-HCC [ 16 ]. Interestingly, three of them (CCNB1, TOP2A, NEK2) were also identified as crucial genes in HCV-HCC, which might to some extent reflect the common transcriptome regulatory mechanisms in liver cancer induced by viral hepatitis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we reported 17 hub genes with diagnostic and prognostic values in HBV-HCC [ 16 ]. Interestingly, three of them (CCNB1, TOP2A, NEK2) were also identified as crucial genes in HCV-HCC, which might to some extent reflect the common transcriptome regulatory mechanisms in liver cancer induced by viral hepatitis.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, all of the four risk signature genes had been reported to play oncogenic roles in HCC and their elevated expression levels were closely related to the reduced overall survival of HCC patients [ 18 27 ], which is in agreement with this study. For example, CCNB1 and AURKA were proved to be significantly associated with the prognosis of HCC and HBV-HCC and proposed as hub genes in these cancers [ 16 , 19 , 25 28 ]. Weng, L. et al demonstrated that the elevated expression of CCNB1 was an independent prognostic indicator for the recurrence in HBV-HCC patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual combination of these novel biomarkers with AFP improved the diagnostic sensitivity of HCC achieved to approximately 90% [138][139][140], depending upon stages. Besides, the integrated bioinformatics analysis based on the HBV-related HCC transcriptome databases suggested the key hub genes with a dysregulated expression profile as potential diagnosis and/or prognosis signatures [141]. However, more prospective lines of evidence from large cohorts and experimental results with solid molecular explanations are needed to support the clinical application of these novel serum biomarkers or genetic tools.…”
Section: Diagnosis Of Hbv-related Hcc By Circulating Virus-host Chimera Tumor Dna Generated By Hbv Integrationmentioning
confidence: 99%
“…As far as the most common inducers of carcinoma-associated mortality in the world, primary liver carcinoma ranks second, thus becoming a great public health challenge [3][4][5]. Primary liver carcinoma consists of liver hepatocellular carcinoma (LIHC), intrahepatic cholangiocarcinoma (iCCA), and other rarely seen neoplasms [6,7]. Mostly, LIHC occurs in patients with chronic liver disease, and it is generally caused by a vicious cycle of liver damage, inflammation, and regeneration that usually span several decades [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%